EXPERIENCE OF TESTICULAR CANCER PATIENT LONG TERM FOLLOW-UP IN TERTIARY REFERRAL HOSPITAL - Nugroho, Prasetyo; Seputra, Kurnia Penta; Medianto (Indonesian Journal of Urology, 2024)
Objective: This study aims to determine the survivability testicular cancer patients at a tertiary hospital in Malang, Indonesia. Material & Methods: This is study conducted from January 2021 to January 2022 at Saiful Anwar General Hospital in Malang, East Java. Involving 32 testicular cancer patients. Data was obtained through medical record January 2017 – January 2022. Analysis was carried out to determine the survivability of the patient. Results: The results showed that the proportion of 1 to 5 year survival rate in testicular cancer patients was 96% and 21%. Kaplan Meier test showed significant difference of patient survival in the radiation therapy exposure (p=0.021), Karnofsky score (p=0.010), tumour type (p=0.019), and response of chemotherapy (p=0.015). Conclusion: The survival rate of testicular cancer patients are strongly influenced by the karnofsky score, radiation therapy exposure, tumour type, and chemotherapy response. Therefore early diagnosis and treatment plays an important role in improving survival rate of the patients. Keywords: Testicular cancer, survival rate, seminoma, non seminoma.